Experimental investigation of red ceramic waste-based alkali-activated binders - Carvalho, Ivo de Castro (2024)
Ordinary Portland cement (OPC) remains one of the most widely used materials in the world and its use is expected to grow due to the continuous demand for new structures, especially in emerging countries. The environmental impact linked to the production of Portland cement is very significant, especially in terms of global warming, since the production process involves high CO2 emissions and generates high energy consumption. Thus, the search for sustainable alternative binders to Portland cement has been a major focus of study and alkali-activated materials (AAMs) are one of the most promising binders and have been studied on a large scale worldwide. Research into new types of precursors is constantly being carried out with a focus on studying the feasibility of new types of alkali-activated mixtures. The investigation of red ceramic waste-blast furnace slag alkali-activated mixtures remains poorly conducted especially regarding its rheological properties and reaction kinetics. This study aims to produce and evaluate the properties of alkali-activated mixtures based on red ceramic waste (RCW) and blast furnace slag (BFS) as precursors. Commercial sodium silicate and sodium hydroxide were used as activators in this research. This alkali activation was performed for mixtures with 3 different RCW contents (25%, 50%, 75%), and 2 silica modulus values (Ms = SiO2/Na2O of the activators). The fresh-state mixtures were submitted to isothermal calorimetry tests, to study the reaction kinetics of the mixtures, flow sweep tests, and oscillatory rheology tests to investigate the agglomeration kinetics and the early age structural build-up based on storage modulus (G’), loss modulus (G’’), and phase angle (δ) parameters. In the fresh state, an in-situ FTIR analysis was also proposed to investigate the Si-O-T band evolution over time in early ages (< 90 min). The pastes were also evaluated in hardened state tests using compressive strength at ages of 3, 7, and 28 days, microstructural analysis using Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TG/DTG). Finally, environmental impact analyses were carried out, identifying reductions in the range of 65% in CO2 emission and energy consumption for the mixtures analyzed, compared to OPC mixtures. RCW contents of up to 50% generated excellent compressive strength results (up to 68.8 MPa at 28 days). In addition, the incorporation of RCW delayed the peak reaction of the pastes and reduced the intensity of Si-O-T bands, by FTIR test. The formation of C(N)-A-S-H was greatly reduced for RCW contents of 75%, remaining similar for contents of 25% and 50%, according to the TG/DTG test. Flow rheology tests indicated a Newtonian-like behavior for the pastes produced, with yield stresses close to zero. In addition, higher RCW contents generated higher viscosities. Oscillatory rheology tests indicated a delay in structural build-up for mixtures with an increase in Ms value, where a later evolution of G' was observed for mixtures with Ms = 1.3. The increase in RCW content also reduced the structural build-up rate of the alkali-activated pastes.